Solid-phase Synthesis of Visible-light-driven BiVO4 Photocatalyst and Photocatalytic Reduction of Aqueous Cr(VI) - Jing Li; Yan Chen; Chengru Chen; Shaorong Wang (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
This communication reports a pioneering study on the synthesis of BiVO4 and photocatalytic reduction of Cr(VI)-polluted wastewaters. Monoclinic phase BiVO4 micron-crystals with adjustable morphology were synthesized via a solid-phase route. The structures, morphology, optical properties of the BiVO4 micron-crystals were characterized by X-ray diffraction, field emission scanning electron microscopy, UV-vis diffuse reflectance spectra, Fourier transform infrared spectroscopy spectra, and photocurrent measurements. Besides, their photocatalytic properties were tested for the reduction of aqueous Cr(VI) under visible light (l > 420 nm) irradiation. The photocatalytic tests showed that the photocatalytic activities of BiVO4 powders in aqueous Cr(VI) depended on the dark adsorption amount for Cr(VI) and number of photogenerated carriers. BiVO4-(c) exhibited the highest photocatalytic reduction efficiency that attributed to highest separation and transfer efficiency of photogenerated electrons and holes. Besides, effects of photocatalytic experiment parameters (including dosage of photocatalyst and coexistent anions and cations) on the Cr(VI) removal rate by BiVO4-(c) were also investigated, and •OH play an important role in the BiVO4 photocatalytic reduction Cr(VI).